The Response of Nutrient Uptake, Photosynthesis and Yield of Tomato to Biochar Addition under Reduced Nitrogen Application - Lili Guo; Huiwen Yu; Mourad Kharbach; Jingwei Wang (Agronomy, 2021)
Tomato is an important economic crop that is widely consumed worldwide. Tomato production is mainly limited by the use of nitrogen fertilizer, sunlight, soil and water conditions. Biochar is one of the soil amendments, and it is recognized as a promising practice for improving crop production in agriculture. The effect of biochar on the photosynthetic traits and tomato yield under reduced nitrogen fertilizer application is still not well understood. The objective of this research is to investigate the influence of biochar application on the photosynthesis and yield of tomato under reduced nitrogen fertilizer application from the perspectives of the nutrient uptake of plants (nitrogen and phosphorus), leaf photosynthetic pigment and leaf gas exchange parameters. Two-year greenhouse experiments containing six biochar levels (0, 10, 30, 50, 70, and 90 t ha−1) and two nitrogen fertilizer application rates (190 and 250 kg ha−1) were conducted. Compared with C0, C50 significantly improved the nitrogen uptake (74–80%) and phosphorus uptake (76–95%) by tomato plants and further enhanced the photosynthetic traits of tomato leaves (net photosynthetic rate (Pn), stomatal conductance (gs), transpiration rate (Tr) and chlorophyll (2–60%), which lead to the highest gains in tomato yield (more than 50%) even when the applied nitrogen fertilizer was significantly reduced (from 250 kg ha−1 to 190 kg ha−1). The photosynthesis rate had a linear correlation with the total nitrogen and phosphorus accumulation and tomato yield. The results will enhance our understandings about the effect of biochar on the photosynthesis and yield of tomato and be of importance for practical agricultural management.